Biological autoluminescence as a noninvasive monitoring tool for chemical and physical modulation of oxidation in yeast cell culture - Bereta, Martin; Teplan, Michal; Chafai, Djamel Eddine; Radil, Roman; Cifra, Michal (Scientific reports, 2021)
Normal or excessive oxidative metabolism in organisms is essential in physiological and pathophysiological processes, respectively. Therefore, monitoring of biological oxidative processes induced by the chemical or physical stimuli is nowadays of extreme importance due to the environment overloaded with various physicochemical factors. Current techniques typically require the addition of chemical labels or light illumination, which perturb the samples to be analyzed. Moreover, the current techniques are very demanding in terms of sample preparation and equipment. To alleviate these limitations, we propose a label-free monitoring tool of oxidation based on biological autoluminescence (BAL). We demonstrate this tool on Saccharomyces cerevisiae cell culture. We showed that BAL can be used to monitor chemical perturbation of yeast due to Fenton reagents initiated oxidation-the BAL intensity changes with hydrogen peroxide concentration in a dose-dependent manner. Furthermore, we also showed that BAL reflects the effects of low-frequency magnetic field on the yeast cell culture, where we observed a disturbance of the BAL kinetics in the exposed vs. control case. Our results contribute to the development of novel techniques for label-free, real-time, noninvasive monitoring of oxidative processes and approaches for their modulation.
Keywords: Saccharomyces cerevisiae; celulosa; Culture Techniques; oxidace-redukce; povidon; Drug Combinations; luminiscence; Oxidation-Reduction; kultivační techniky; fixní kombinace léků; Cellulose; Luminescence; Povidone